Seasonal Variation of Febrile Seizures in Children Aged 6 Months to 5 Years: A Cross-Sectional Study in Shahroud, Iran - Saeedi , Fateme; Yoysefi , Elnaz; Zolfaghari , Pouneh; Salari Zare , Mohammad; Sohrabi, Mohammad Bagher; Janmohamadi, Farahnaz; Rashidan, Marjan (Shahroud Journal of Medical Sciences, 2025)
Background: Circadian rhythms are actually daily periodic fluctuations in the organism's physiology, metabolism or behaviour. Among the areas of the brain that were seen to have a pattern of daily changes are the areas related to reward. The aim of this study was to investigate seasonal changes in febrile seizures in children aged 6 months to 5 years in Shahroud city.Methods: This descriptive cross-sectional study was conducted retrospectively on patients’ records. Investigators assessed the records of patients with simple FS aged 6 to 60 months referred to Emergency Department of Bahar Hospital, Shahroud, Iran during March 2021 to March 2022. Data were gathered by a checklist including age, sex, temperature, seasonal, months, diurnal variation and simple or complex FS.Results: Out of 97 children examined, 51 (52.6%) were boys and the rest were girls with an average age of 24.4±14.6 months. The mean temperature of patients was 38.5±0.7 °C. Simple FS was 77 (79.4%) and complex FS was 20 (20.6%). Most of the FS occurred in afternoon 31 (32%) and in April and December 15 (15.5%). Autumn had the highest proportion 29 (29.9%), while summer had the lowest 15 (15.5%). It was also found that there is a significant relationship between the age group of patients and the season of FS (P-value=0.016) and it is more in spring and autumn.Conclusions: The present study showed that the occurrence of FS has a specific circadian rhythm, so that it is more in the spring and autumn seasons and in the afternoon hours, and it is necessary to monitor children with fever, especially at the age of one to two years. be placed in these times.